An Unusual Skin Adverse Event after Switching from Intravenous to Subcutaneous VEDOLIZUMAB Therapy in Patients with Ulcerative Colitis - Peaucelle, Anne-Sophie; Gay, Claire; Lefevre, Marine-Alexia; Barrau, Mathilde; Boschetti, Gilles; Nancey, Stéphane; Roblin, Xavier (Archives of Clinical and Medical Case Reports, 2023)
Here, we report for the first time 2 cases of patients with ulcerative colitis (UC) (55 and 35 years old women) in clinical remission under maintenance regimen under vedolizumab infusions 300 mg every 8 weeks. After having switched the patients to subcutaneous (sc) vedolizumab 108 mg every two weeks, both patients experienced urticaria like skin lesions located on the site of drug injection with favorable outcomes. Both were then back switched to infusion of vedolizumab and surprisingly developed again at the same previous spot similar and reversible urticaria like skin lesions.